The effect of context on the semantic change on the Quranic text in the sentence - جواد الغراوي, قصي; حيدر عبد الرضا, أنفال (Journal of College of Education, 2020)
The Quranic sentence is the basis upon which the entire Qur'anic text is based. It is the entity that organizes the Quranic vocabulary, It plays its role in conveying the intended meaning of the text. Context comes as an effective factor in guiding the meaning of the term, and then, the entire Quranic sentence, as it leads to the understanding of the intent of the Quranic text, which requires an accurate knowledge of the meaning of the context.The Quranic sentence is characterized by a specific context, based on the interconnectedness of the posterior to the previous. The grammatical functions and the syntactic structure of the sentence play a major role in the syntax, which indicates grammatical coherence, which is consistent with the semantic cohesion of it, that (the variation in the Quranic sentence and its effect on the context), and the connection of the Qur’anic sentence to its context. The elements of the Qur’anic sentence combined to perform the intended Qur’anic meaning, which shows that the meanings of the holy Qur’an relate to the letter, the pronunciation, and the sentence, so that all of the above are consistent in the performance of its meanings and purposes.This shows that if the sentences meanings were the same as the vocabulary’s meaning, then the use of sentences and understanding their meanings would depend on their transmission from the Arabs as the vocabulary was as well.I mentioned the Quranic context, and its effect on the meanings of: letters- vocabulary- sentences, in the Holy Qur’an, and the effect of the Quranic context on the general indications of Quranic sentences, so the verses are related to each other in particular, and the context plays its role in highlighting the general meaning, in a coherent semantic manner.